Verb Aspect in the Malay Dialect Sekadau: an Introduction: (Aspek Kata Kerja dalam Dialek Melayu Sekadau: Suatu Pengenalan) (Jurnal Bahasa, 2014)
This paper examines the aspects of verbs in the Malay Sekadau dialect by looking at the verb roots, as well as active, passive and anti-passive markers. The dialect is spoken  in Sekadau, which is located about 300 km from Pontianak-the capital city of West Kalimantan, Indonesia. In this area, the Sekadau Malay dialect functions as the lingua franca for the community. Here, this dialect is the mother tongue of the Malays, and the language of interaction for the Chinese and Dayaks. So far, there have only been a few studies attempting to discuss verbs in Sekadau Malay. This study finds that a noun can be transformed into a verb without any morphological change; the N- prefix is an active marker; the prefix d- is a passive marker, while the prefix be- is an antipassive marker.Keywords: Sekadau Malay dialect, verbs, active, passive, antipassive